2022
DOI: 10.32074/1591-951x-734
|View full text |Cite
|
Sign up to set email alerts
|

Pathologist’s approach to paediatric and neonatal eosinophilic gastrointestinal disorders

Abstract: Summary Children are not simply miniature adults. The evaluation of their gastrointestinal disorders is therefore different from that in full-grown adults and requires a particular clinical/pathologic approach. Different studies have tried to assess the normal eosinophil distribution in the gastrointestinal tract in adults while very few studies have investigated the paediatric population, consequently complicating the pathologist’s ability in identifying an abnormal number of eosinophils… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 69 publications
0
6
0
Order By: Relevance
“…The differential diagnosis with celiac disease, infective gastroenteritis, eosinophilic gastroenteritis, allergic gastroenteritis, autoimmune colitis, should be taken in consideration. For these entities, we invite the reader to refer to other papers in this Special Issue for a more in-depth discussion of these conditions 18 , 28-31 . Some peculiar ‘minimal histological lesions’ have been described in VEO-IBD, and are reported to be more frequent with respect to IBD arising in older patients.…”
Section: Histological Findingsmentioning
confidence: 99%
“…The differential diagnosis with celiac disease, infective gastroenteritis, eosinophilic gastroenteritis, allergic gastroenteritis, autoimmune colitis, should be taken in consideration. For these entities, we invite the reader to refer to other papers in this Special Issue for a more in-depth discussion of these conditions 18 , 28-31 . Some peculiar ‘minimal histological lesions’ have been described in VEO-IBD, and are reported to be more frequent with respect to IBD arising in older patients.…”
Section: Histological Findingsmentioning
confidence: 99%
“…Known drug triggers of EC reported in the literature are nonsteroidal anti-inflammatory drugs, antiplatelet drugs, tacrolimus, and carbamazepine. 1,7–11 A study by Casella et al demonstrated an association between the use of antiplatelets (and other drugs) and an increased eosinophilic infiltration limited to the descending and sigmoid colon, even without symptoms, and in our patient, we decided—after specialist consultation—to discontinue clopidogrel. 11 After drug withdrawal, our patient experienced a rapid remission of symptoms that supported our suspicion of clopidogrel-induced EC, and histology obtained during endoscopy performed 3 months after drug discontinuation confirmed this hypothesis.…”
Section: Discussionmentioning
confidence: 65%
“…As in previous reports of cryobiopsy, ROSE slide preparation was also possible using specimens obtained by non-intubated cryobiopsy [24, 25]. In diagnosing PPLs with bronchoscopy, the primary purpose is often the collection of tumor cells, which have distinctive histopathological features that can be recognized even in small samples, from the precise location of the target lesion through the related bronchus [21, 26, 27]. Therefore, most cases with PPLs require a smaller amount of tissue specimen than that of interstitial lung disease for diagnosis.…”
Section: Discussionmentioning
confidence: 99%